Peran Strategis Madrasah Swasta di Indonesia - Solahudin Solahudin (Institut Agama Islam Negeri Purwokerto, 2018)
This paper is aimed at discussing the strategic role of school (madrasah) in the country. Madrasah is one of the Islamic educational institutions that have an important role for the development of Islamic education in Indonesia. Madrasah is a place to galvanize the mental, moral, and spiritual of the young generation to educate students to be useful beings for the religion, state, and nation. Private Madrasahs as one of the Islamic Education Institutions in Indonesia have a strategic role in the participation of the nation's intellectuals. In the next developments, private madrasahs face complex issues. In one hand, there is a demand to improve the quality in order to compete with state Islamic education institutions and public schools, but on the other hand, the attention of the government, both central and local, to Islamic educational institutions is still low, even they are still placed not as the main class, but the second class of education institutions. The Ministry of Religious Affairs, which became the central policy, began to formulate serious efforts to improve the quality of madrasahs, such as through the Ministry's Strategic Plan.